2005
DOI: 10.1016/j.bbrc.2005.08.091
|View full text |Cite
|
Sign up to set email alerts
|

First evidence that cytochrome P450 may catalyze both S-oxidation and epoxidation of thiophene derivatives

Abstract: Oxidation of 2-phenylthiophene (2PT) by rat liver microsomes, in the presence of NADPH and glutathione (GSH), led to three kinds of metabolites whose structures were established by 1H NMR and mass spectrometry. The first ones were 2PT-S-oxide dimers formed by Diels-Alder type dimerization of 2PT-S-oxide, while the second ones were GSH adducts derived from the 1,4-Michaël-type addition of GSH to 2PT-S-oxide. The third metabolites were GSH adducts resulting from a nucleophilic attack of GSH to the 4,5-epoxide of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 32 publications
2
75
0
Order By: Relevance
“…Although we could not definitely characterize the incorporated position of GSH and oxygen at the thiophene ring, another GSH conjugate (B2, isomer of B1) was also detected. Dansette et al (2005) reported interesting MS/MS fragment analyses on the two GSH conjugates of 2-phenylthiophene, in which the loss of 48 amu (sulfoxide) was favored over the loss of 18 amu (water) in the case of the GSH conjugate of the thiophene S-oxide, whereas the loss of 18 amu was dominant in the case of 5-hydroxy-4-glutathionyl-4,5-dihydrothiophene resulting from the addition of GSH to the thiophene epoxide. However, another thiophene GSH adduct of S-oxide showed no loss of 48 amu but did show a loss of 18 amu in the product ion spectrum (Medower et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not definitely characterize the incorporated position of GSH and oxygen at the thiophene ring, another GSH conjugate (B2, isomer of B1) was also detected. Dansette et al (2005) reported interesting MS/MS fragment analyses on the two GSH conjugates of 2-phenylthiophene, in which the loss of 48 amu (sulfoxide) was favored over the loss of 18 amu (water) in the case of the GSH conjugate of the thiophene S-oxide, whereas the loss of 18 amu was dominant in the case of 5-hydroxy-4-glutathionyl-4,5-dihydrothiophene resulting from the addition of GSH to the thiophene epoxide. However, another thiophene GSH adduct of S-oxide showed no loss of 48 amu but did show a loss of 18 amu in the product ion spectrum (Medower et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of 18 O into the 5-hydroxythiophene metabolite indicated an epoxide intermediate pathway (Dalvie et al, 2002;O'Donnell et al, 2003). Furthermore, in the study of bioactivation of 2-phenylthiophene by rat liver microsomes in the pres- ence of GSH, a metabolite was isolated and identified as the product of GSH nucleophilic attack to the 4,5-epoxide of 2-phenylthiophene (Dansette et al, 2005). This provided direct evidence for the epoxidation pathway in thiophene metabolic activation.…”
Section: Discussionmentioning
confidence: 88%
“…The S-oxidation and epoxidation mechanisms have been widely accepted for the metabolic activation for thiophene derivatives. The S-oxidation mechanism was supported by evidence of the formation of thiophene S-oxide in vitro and in vivo or its 1,4-Michael addition product or sulfoxide dimers from the DielsAlder dimerization (Dansette et al, 2005;Medower et al, 2008). The epoxidation mechanism is supported by indirect evidence with bioactivation of 2-(4-methoxybenzoyl)thiophene in the presence of 18 O 2 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations